Pengaruh DER, CR, DPR, EPS, Inflasi, Dan Pertumbuhan Arus Kas Operasi Terhadap Return Saham Pada Perusahaan Sektor Property, Real Estate dan Konstruksi Bangunan Di BEI - Bayu Wulandari; William Wijaya; Veronika Winata; Kathy Kathy; Lise Septani (COSTING : Journal of Economic, Business and Accounting, 2021)
The purpose of this research is to carry out analysis regarding the influence of Operating Cash Flow Growth, Inflation, Earning per Share Ratio, Debt to Equity Ratio, and Current Ratio on Stock Returns in building, property, and real estate construction companies. In the implementation of this research, the population used is building construction companies, property, and real estate which are listed on the Indonesia Stock Exchange for the period 2016 to 2019. In this study, the sampling technique is using purposive sampling. The data used are quantitative secondary data. The data analysis method is multiple linear regression. Based on the results of the analysis, it is determined that simultaneously the independent variable Debt Equity Ratio, the independent variable Current Ratio, the independent variable Earning per Share, the independent variable Dividend Payout Ratio, Inflation and Growth in Operating Cash Flow do not provide contribution to the influence of Stock Return. Partially the results of the analysis determine that the independent variable of the Debt Equity Ratio contributes a significant effect on stock returns, meanwhile for the independent variables of Current Ratio, Dividend Payout Ratio, Earning per Share, Inflation and Operating Cash Flow Growth did not contribute significantly to Stock Returns. Keywords: Debt Equity Ratio, Current Ratio, Dividend Payout Ratio, Earning Per Share, Inflation, Operating Cash Flow Growth and Stock Returns